2005
DOI: 10.1086/427148
|View full text |Cite
|
Sign up to set email alerts
|

Severe Community-Onset Pneumonia in Healthy Adults Caused by Methicillin-Resistant Staphylococcus aureus Carrying the Panton-Valentine Leukocidin Genes

Abstract: To our knowledge, these patients represent the first reported North American adults with severe community-onset MRSA pneumonia caused by strains carrying the PVL genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
490
3
7

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(514 citation statements)
references
References 32 publications
14
490
3
7
Order By: Relevance
“…Type I ACME has been postulated to contribute to growth and survival of USA300 within the host, and promote colonization of the human skin [26]. ACME is integrated downstream of type IV SCCmec (Figure 2), utilizing the same cassette chromosome recombinases A and B (ccrAB) contained with SCCmec for mobilization and transfer [15][16][17][18][19][20][21][22][23][24]34]. Type I ACME is a distinctive genetic feature of the USA300 pandemic clone [26,34,35], although ACME-like elements have been detected in sporadic MRSA [32][33][34].…”
Section: Unique Genomic Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Type I ACME has been postulated to contribute to growth and survival of USA300 within the host, and promote colonization of the human skin [26]. ACME is integrated downstream of type IV SCCmec (Figure 2), utilizing the same cassette chromosome recombinases A and B (ccrAB) contained with SCCmec for mobilization and transfer [15][16][17][18][19][20][21][22][23][24]34]. Type I ACME is a distinctive genetic feature of the USA300 pandemic clone [26,34,35], although ACME-like elements have been detected in sporadic MRSA [32][33][34].…”
Section: Unique Genomic Contentsmentioning
confidence: 99%
“…Pneumonia is a rare disease caused by CA-MRSA [17,24]. Using purified toxin or a laboratory strain of S. aureus that overproduced PVL via a multicopy plasmid, PVL was shown to impact mouse survival in a model of pneumonia using BALB/c mice [47].…”
Section: Pvl In Experimental Pneumonia: An Exception?mentioning
confidence: 99%
See 1 more Smart Citation
“…This also extends the finding of previous case studies reporting that MRSA CAP with PVL toxin is associated with worse outcomes. [24][25][26][27][28][29][30] Moreover, we clearly document that PVL-positive strains are emerging as a cause of pulmonary infection in broader clinical scenarios. As such, physicians must remain vigilant for this toxin-producing strain.…”
Section: Discussionmentioning
confidence: 88%
“…23 Recent studies of acute pneumonia with animal models and in humans have suggested that the PVL toxin-alone or in combination with other virulence factors-is associated with the development of necrotizing pneumonia. [24][25][26][27][28][29][30] In our study, 23 patients with MRSA CAP had strains that contained PVL toxin, and these patients had longer stays in hospital and higher total hospital charges than those with MRSA CAP not containing the PVL toxin. This is an important finding, as length of stay is an important proxy for morbidity and case severity.…”
Section: Discussionmentioning
confidence: 93%